The knowledge society from popular multiculturalism and virtual surroundings of learning - Sonia Mª Santoveña Casal (Foro de Educación, 2011)
The knowledge society is defined by multiculturalism, by variety in forms of expression and content. To understand the process of building social networks and new styles of cultural expression that are being developed, it is necessary to participate and experience what we are trying to teach. From school, we are talking about a reality that we do not know. A reality that is changing rapidly, where its true creators: young people, do not talk about it, but live and transform it. The acceptance from the education of different ways of comunication and exchange between students, could make easier the development and help us to harness the resources of the Internet, a network rich in expression, creativity and communication.